2022
DOI: 10.3390/ijerph20010745
|View full text |Cite
|
Sign up to set email alerts
|

Examining Psychosocial and Economic Barriers to Green Space Access for Racialised Individuals and Families: A Narrative Literature Review of the Evidence to Date

Abstract: Background: Social prescribing (such as green social prescribing), aims to address health disparities cross-culturally to improve well-being. However, evidence highlights racial disparities in relation to access to quality green space (including local/national parks and recreational spaces). This review aimed to identify the psycho-socioeconomic barriers to green space access for racialised individuals/families and Black Indigenous People of Colour (BIPOC), to understand what cultural adaptations might be made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Uptake data suggest more women and white, affluent, and older people receive a social prescription 15. Factors affecting accessibility include infrastructural barriers (eg, transport) and cultural perceptions about nature 16. However, appropriately targeted and funded activity, with barriers addressed, can reach excluded communities such as refugees or people with substance use disorders 1718…”
Section: Health Benefitsmentioning
confidence: 99%
“…Uptake data suggest more women and white, affluent, and older people receive a social prescription 15. Factors affecting accessibility include infrastructural barriers (eg, transport) and cultural perceptions about nature 16. However, appropriately targeted and funded activity, with barriers addressed, can reach excluded communities such as refugees or people with substance use disorders 1718…”
Section: Health Benefitsmentioning
confidence: 99%
“…This review identified that an individuals’ perception of the safety of an environment may impact the benefits observed; 45 a barrier that has widely been reported within the field of green space literature. 96 99 Perceived environmental safety and fear of crime is a particular concern for those of older age, 100 and for racialised individuals. 99 While recorded crime rates are substantially greater in the most socio-economically deprived areas, 101 research has shown that access to nature and NBIs can have a mitigating impact on violence.…”
Section: Discussionmentioning
confidence: 99%
“… 96 99 Perceived environmental safety and fear of crime is a particular concern for those of older age, 100 and for racialised individuals. 99 While recorded crime rates are substantially greater in the most socio-economically deprived areas, 101 research has shown that access to nature and NBIs can have a mitigating impact on violence. 102 As such urban planning initiatives should consider the two-way interaction between perceived environmental safety and NBI engagement for socio-economically deprived communities.…”
Section: Discussionmentioning
confidence: 99%
“…First, we additionally adjusted the main model for ethnicity (both parents born in Belgium, one or both parents born abroad) and for time of examination (one at a time). The rationale to adjust for ethnicity is the possibility of ethnic inequalities in green space availability [ 37 ] or use [ 38 ]. Second, to test the association between agricultural area around the residence and the cognitive outcomes, we replaced green space with agricultural area in the main model.…”
Section: Methodsmentioning
confidence: 99%